Placental telomere length decline with gestational age differs by sex and TERT, DNMT1, and DNMT3A DNA methylation. (December 2016) - Wilson, Samantha L.; Liu, Yao; Robinson, Wendy P.
Abstract: Introduction: Telomere length (TL) has been suggested to be influenced by inherited genetic and epigenetic variation, hormonal effects, oxidative stress and age. However, the dynamics of TL during in utero development have not been well explored. This study investigates the relationship between placental TL and sex, gestational age (GA), and DNA methylation (DNAm). Placental TL is further evaluated in pregnancies complicated by preeclampsia (PE) and intrauterine growth restriction (IUGR), conditions hypothesized to lead to decreased placental TL due to increased oxidative stress. Methods: Average TL in 21 early-onset PE (EOPE), 18 late-onset PE (LOPE), 9 IUGR, 59 viable and 33 non-viable control placentas were measured by qPCR. Of these, 13 control, 20 EOPE, 17 LOPE, and 8 IUGR samples were also run on the Illumina 450K array. ANOVA was used to compare TL between controls and EOPE, LOPE, and IUGR. Linear regression correcting for GA and sex, assessed the association between TL and DNAm in biologically-relevant genes ( TERC, TERT, DNMT1, DNMT3a, DNMT3b ), and array-wide. Results: Male sex and increasing GA were associated with shorter placental TL. Correcting for these factors, no significant difference in TL was observed between EOPE, LOPE, and IUGR placentas compared to controls. Targeted analysis revealed TL was associated with DNAm at TERT, DNMT1, and DNMT3a . An array-wide approach found no additional sites associated with TL. Conclusion: Variability in placental TL is associated with alterations in DNAm at TERT, DNMT1, and DNMT3a . Placental TL is not strongly influenced by EOPE, LOPE, or IUGR. Highlights: Male sex and gestational age negatively associate with placental telomere length. Placental telomere length was not altered in preeclampsia or IUGR. Telomere length was associated with altered DNAm within TERT, DNMT1, and DNMT3a.